110 DEVELOPMENT AND DELIVERY OF A MULTI-DISCIPLINARY HYBRID EDUCATION PROGRAM IN SYNCOPE AND RELATED DISORDERS DURING THE COVID-19 PANDEMIC. (25th October 2022) - Rice, C; Byrne, L; Ortuno, RR; Kenny, RA; Cunningham, C; Govern, MM; Dsouza, A; Prabhukeluskar, S; Quinlan, P
Abstract: Background: Syncope and related disorders is an important area for training of all health professionals. During the COVID-19 pandemic, we adapted the delivery of our annual face-to-face certified program to a 9-month hybrid program. Here, we describe the development, delivery, and evaluation of such new program. Methods: A pre-existing curriculum was modified to incorporate online content, online lecture delivery and interactive group learning, in addition to individual practical placements in a syncope management unit, in line with government and hospital infection control guidance at the time. Monthly content included video consultant case presentations, ECG analysis and interpretation, and instructional videos of diagnostic testing and relevant technologies. A comprehensive online week-long lecture program was developed. Results: The lecture week included 30 clinical lectures, 10 clinical case presentations and 10 'how to' practical videos for testing/monitoring procedures. Further learning over zoom incorporated learner case presentations in a small group format. At the completion of the course the leaners attended a final online half day of lectures and completed the multi choice question examination. Conclusion: "Thank you so much for putting together such a fantastic week of training." "The quality and expertise of the speakers was outstanding." "I have taken a huge amount away to incorporate into my practice and local unit." The above learner feedback is consistent with our aim to deliver a high-quality specialist program for those interested in advancing the management of syncope and related disorders. Over time, this specialist training will aid the development of regional syncope management units across Ireland. The benefits of a hybrid learning model include multiple options to cater for all categories of learners, thus suggesting it is the cornerstone of future learning modalities.